Business4Land Strategic Workshop outcome report - United Nations Convention to Combat Desertification (United Nations Convention to Combat Desertification, 2025)
A report on the Business4Land Strategic Workshop describing main presentations and outcomes, and to which ILRI contributed through the project STELARR (Sustainable Large-Scale Investments for Rangeland Restoration).